Effect of Addition of Cod Liver Oil in the Commercial Feed Protein Retention and Retention Energy Meat Giant Freshwater Prawn (Macrobrachium rosenbergii) - Fajar Septian Aji; Boedi Setya Rahardja; Agustono agustono (Journal of Marine and Coastal Science, 2019)
Prawns (Macrobrachiumrosenbergii) is one of the freshwater shrimp species native to Indonesia. Shrimp prawns are the most popular of all freshwater shrimp because of its large size and has a high economic value in both domestic market and abroad. Problems commonly encountered in the cultivation of prawns currently includes several factors such as water quality, disease and feed. Efforts that can be done is by feeding in sufficient quantity and quality and not excessive is a very decisive factor. Technical constraints on the level of farmers are limited in supply mains quality. Therefore, efforts are needed to tackle these problems by managing the stock of prawns parents. This study aims to determine the addition of cod liver oil on a commercial feed can increase protein retention and energy retention prawns (Macrobrachium rosenbergii). This research was carried out experimentally with a completely randomized design (CRD). The treatments were given a dose of cod liver oil 0% (control), and the treatment 1-4 using a 3% increase each treatment dose. Analysis of data using ANOVA followed by Duncan test. Based on the research results giving cod liver oil on a commercial feed effect on increasing protein retention and energy retention of lobster meat. Retention of the best protein found in 4 treatments with a dose of 12%, while the retention of the best energy contained in the second treatment with a dose of 6%.